2012
DOI: 10.1007/s00464-012-2424-z
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits and virtual reality performance

Abstract: Background Surgeons' personalities have been described as different from those of the general population, but this was based on small descriptive studies limited by the choice of evaluation instrument. Furthermore, although the importance of the human factor in team performance has been recognized, the effect of personality traits on technical performance is unknown. This study aimed to compare surgical residents' personality traits with those of the general population and to evaluate whether an association ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Openness is also critical in team settings. In a study among surgeons, personal traits such as openness demonstrated "an important role in team performance, which in turn is highly relevant for optimal surgical performance" (Rosenthal et al, 2013). VR is proven to be "particularly useful for promoting change within students' conceptualizations of representation, narrativity and affect" (Dittmer, 2010), thus promoting the notion of openness.…”
Section: Opennessmentioning
confidence: 99%
“…Openness is also critical in team settings. In a study among surgeons, personal traits such as openness demonstrated "an important role in team performance, which in turn is highly relevant for optimal surgical performance" (Rosenthal et al, 2013). VR is proven to be "particularly useful for promoting change within students' conceptualizations of representation, narrativity and affect" (Dittmer, 2010), thus promoting the notion of openness.…”
Section: Opennessmentioning
confidence: 99%
“…Compared to the general population, the cohort showed less neuroticism, more extroversion and conscientiousness, and male residents showed greater openness. Despite these differences from the general population, none of the various personality styles were found to be associated with performance on the virtual reality simulator (technical performance) 11 . Thus, personality inventories may play a more important role in the non-technical aspects of residency training such as team performance.…”
Section: Introductionmentioning
confidence: 89%
“…Well-designed video games can have enough flexibility and richness to allow assessment of a large number of traits and dispositions simultaneously within a relatively short session. In a previous report the authors used a personality NEO-Five Factor Inventory (FFI) to identify specific personality traits in a cohort of surgeon trainees and medical students and compared performance in a simulated operating room 11 . They compared the personality traits of the cohort to a sample from the general population and to each other based upon performance on a laparoscopic simulator.…”
Section: Introductionmentioning
confidence: 99%
“…Rosenthal et al did not find any significant association. 6 Lovejoy et al however showed that surgeons with low extraversion (i.e. introverted surgeons) tended to have better outcomes which is interesting given the consistent reports of higher extraversion in surgeons compared with the general population.…”
Section: Introductionmentioning
confidence: 94%
“…Rosenthal et al investigated the relation between surgical VR performance-parameters and personality, based on the results of the personality test NEO-Five Factor Inventory. 6 The NEO-FIVE Factor Inventory is a personality inventory that examines a person's Big Five personality traits (openness to experience, conscientiousness, extraversion, agreeableness, and neuroticism). Rosenthal et al did not find any significant association.…”
Section: Introductionmentioning
confidence: 99%